NSM CFRP prestressing techniques with strengthening potential for simultaneously enhancing load capacity and ductility performance - Rezazadeh, Mohammadali (2016)
The ductility performance of reinforced-concrete (RC) members strengthened with carbon-fiber-reinforced-polymer (CFRP) reinforcement using near-surface-mounted (NSM) technique has a tendency to decrease with the increase of the prestress level applied to the CFRPs. Hence, in the current study, first to assure a sufficient degree of ductility for these prestressed members, a methodology was proposed to determine the maximum prestress level that can be applied to the NSM CFRP reinforcement. Using this methodology, a simplified analytical formulation was developed to determine this maximum allowable prestress level. In the second part, after demonstrating the good predictive performance of a developed 3D finite-element (FE) model, first the effect of partial unbonding of prestressed NSM CFRP reinforcement at mid-span to increase the ductility performance of strengthened slabs was numerically assessed. Then, a new hybrid-partially bonded system, combining the fully bonded non-prestressed and partially bonded prestressed CFRP reinforcements in the same application according to NSM technique, was proposed for the flexural strengthening of RC slabs. This hybrid-partially bonded system was capable of providing a better balance in terms of load carrying and ultimate deflection capacity of prestressed strengthened slabs. At the end, a comparison between the potentialities of fully bonded system, partially bonded and hybrid-partially bonded systems for the flexural strengthening of RC structures is made, and the relevant results are presented and discussed.